Liquid crystal polyester resin composition, and molding comprising the same
Patent Information
- Application Number
- JP2024119179
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-08
- Filing Date
- 2024-07-25
- Publication Date
- 2025-02-21
Smart Images

Figure 2025026357000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystal polyester resin composition and a molded article made of the same. More specifically, the present invention relates to a liquid crystal polyester resin composition and a molded article obtained by using the same. [Background technology]
[0002] Liquid crystal polyester resins have excellent heat resistance, fluidity, and dimensional stability, and are therefore used in electrical and electronic components that require these properties. In recent years, the miniaturization of smartphones and other devices has led to a growing demand for higher integration, thinner walls, lower heights, and other components, and liquid crystal polyester resins with improved fluidity are in demand.
[0003] In order to improve fluidity and heat resistance, a liquid crystal polyester resin composition containing a plate-like filler that is easily oriented has been disclosed. For example, Reference 1 discloses that a liquid crystal polyester resin composition with improved physical properties can be obtained by compounding a liquid crystal polyester resin with a controlled terminal substrate with mica having a controlled aspect ratio and average particle size. Reference 2 discloses that blister resistance and heat resistance can be improved by compounding a plate-like inorganic filler with a controlled pH and particle size with a liquid crystal polyester resin. Reference 3 discloses that various properties can be improved by compounding a plate-like filler with a liquid crystal polyester resin having a specific structural unit. On the other hand, due to the complexity of the shape of parts in recent years, injection molding has become more common under high temperature and high shear conditions in order to fill thin parts, and molding is sometimes performed at a high cycle to increase productivity. However, in the conventional technology, when molding is performed under such harsh conditions as described above, stringing during molding (a phenomenon in which the resin stretches in a string-like shape from the top of the sprue when the mold is opened) occurs, which leads to a decrease in productivity, and therefore a liquid crystal polyester resin composition with excellent stringing resistance is required. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2013 / 128887 [Patent Document 2] International Publication No. 2017 / 051883 [Patent Document 3] International Publication No. 2018 / 101214 Summary of the Invention [Problem to be solved by the invention]
[0005] If the viscosity of liquid crystal polyester resin is reduced to ensure fluidity, it becomes easier for air to be entrained during molding, which pushes the resin out from the tip of the molding machine, making it more likely to become stringy. The same is true when molding is done under high temperature and high injection speed (high shear) conditions to ensure fluidity. In addition, plate-shaped fillers are often used as fillers for liquid crystal polyester resin to increase fluidity, but because plate-shaped fillers have good orientation, the resin present from the top of the sprue of the molded product to the tip of the nozzle of the molding machine also becomes highly oriented, so when high temperature, high shear and high cycle conditions are used, the highly oriented parts tend to stretch into threads when the mold is opened. In other words, there is a trade-off between fluidity and stringing resistance.
[0006] An object of the present invention is to provide a liquid crystal polyester resin composition which is less likely to cause stringiness even when injection molded under high temperature, high shear and high cycle conditions, and a molded article made from the same. [Means for solving the problem]
[0007] As a result of extensive research to solve the above problems, the inventors have discovered that a liquid crystal polyester resin composition comprising a liquid crystal polyester resin containing 20 to 80 mol % of the following structural units derived from aromatic hydroxycarboxylic acid, 10 to 40 mol % of structural units derived from aromatic diol, and 10 to 40 mol % of structural units derived from aromatic dicarboxylic acid, relative to 100 mol % of all structural units of the liquid crystal polyester resin, and a plate-like filler, and that by controlling the particle size of the plate-like filler in the composition within a specific range, excellent stringiness resistance during high-temperature molding can be achieved, thereby arriving at the present invention.
[0008] That is, the present invention is as follows: (1) A liquid crystal polyester resin composition containing 10 to 100 parts by weight of a plate-like filler (B) as an inorganic filler, based on 100 parts by weight of a liquid crystal polyester resin (A) containing 20 to 80 mol % of structural units derived from aromatic hydroxycarboxylic acid, 10 to 40 mol % of structural units derived from aromatic diol, and 10 to 40 mol % of structural units derived from aromatic dicarboxylic acid, relative to 100 mol % of all structural units of the liquid crystal polyester resin (A), wherein the particle size of the plate-like filler (B) in the liquid crystal polyester resin composition satisfies the following requirement (α): Requirement (α): The particle size (D70) at 70% cumulative frequency, obtained from the cumulative particle size distribution curve of the plate-like filler (B) in the liquid crystal polyester resin composition, is 25 to 45 μm, and the particle size (D30) at 30% cumulative frequency is 15 to 25 μm. (2) The liquid crystal polyester resin composition according to (1), wherein the liquid crystal polyester resin (A) is a liquid crystal polyester resin containing the following structural unit (I) and satisfies the following formula (a): 1≦[I]≦20 (a) ([I] indicates the content (mol %) of each of the following structural units (I) relative to 100 mol % of all structural units in the liquid crystal polyester resin (A).)
[0009] [ka]
[0010] (3) The liquid crystal polyester resin composition according to (1) or (2), wherein the liquid crystal polyester resin (A) is a liquid crystal polyester resin containing the following structural units (I) and (II) and satisfies the following formulae (b) and (c). 0.01≦[II]≦5 (b) [II] / [I]<1 (c) ([I] and [II] indicate the contents (mol %) of the following structural units (I) and (II) relative to 100 mol % of all structural units in the liquid crystal polyester resin (A).)
[0011] [ka]
[0012] (4) The liquid crystal polyester resin composition according to any one of (1) to (3), wherein the liquid crystal polyester resin (A) is a liquid crystal polyester containing the following structural units (II) and (III) and satisfies the following formula (d): 0.92<[III] / ([II]+[III])<1 ···(d) ([II] and [III] indicate the contents (mol %) of the following structural units (II) and (III) relative to 100 mol % of all structural units in the liquid crystal polyester resin (A).)
[0013] [ka]
[0014] (5) A molded article made of the liquid crystal polyester resin composition according to any one of (1) to (4). (6) The molded article according to (5), which is any one selected from the group consisting of a connector, a relay, a switch, a coil bobbin, and an actuator part of a camera module. Effect of the Invention
[0015] The liquid crystal polyester resin composition of the present invention has excellent resistance to stringiness during high-temperature molding, and can be suitably used in molding small electric and electronic parts, in particular. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a schematic diagram showing a cumulative particle size distribution curve of a plate-like filler in a liquid crystal polyester resin composition. [Diagram 2] FIG. 2 is a schematic diagram of a molded product used in the gate clogging evaluation in the examples.
[0017] P: Perspective view, Q: Side view, R: Top view DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below.
[0019] <Liquid crystal polyester resin (A)> The liquid crystal polyester resin (A) is a polyester that forms an anisotropic molten phase. Examples of such polyester resins include polyesters composed of structural units selected from oxycarbonyl units, dioxy units, dicarbonyl units, etc., which will be described later, so as to form an anisotropic molten phase.
[0020] Next, the structural units constituting the liquid crystal polyester resin (A) will be described. The liquid crystal polyester resin (A) of the present invention contains, as oxycarbonyl units, 20 to 80 mol % of structural units derived from aromatic hydroxycarboxylic acid relative to 100 mol % of all structural units of the liquid crystal polyester resin (A). If it is less than 20 mol %, liquid crystallinity is impaired, making melt molding difficult. It is preferably 25 mol % or more, more preferably 30 mol % or more. On the other hand, if it is more than 80 mol %, melt molding is difficult. It is preferably 75 mol % or less, more preferably 70 mol % or less, and even more preferably 55 mol % or less.
[0021] The liquid crystal polyester resin (A) of the present invention preferably contains 2 to 20 mol % of the structural unit (I) as a structural unit derived from an aromatic hydroxycarboxylic acid. The structural unit (I) is a structural unit derived from 6-hydroxy-2-naphthoic acid. The structural unit (I) is a naphthalene structure, is bulky, and disrupts the linearity of the molecular chain, and therefore promotes entanglement of the molecular chains of the liquid crystal polyester resin (A) during heating and retention, thereby improving the stringing resistance during high-temperature molding. From the viewpoint of stringing resistance, it is preferably 2.5 mol % or more, more preferably 3 mol % or more. Also, it is preferably 15 mol % or less, more preferably 10 mol % or less.
[0022] [ka]
[0023] From the viewpoint of excellent threading resistance, the liquid crystal polyester resin (A) of the present invention preferably contains 15 to 75 mol % of structural unit (IV) as a structural unit derived from an aromatic hydroxycarboxylic acid. More preferably, it is 25 mol % or more, and even more preferably, it is 35 mol % or more. Also, it is preferably 65 mol % or less, and more preferably 55 mol % or less. The structural unit (IV) is a structural unit derived from p-hydroxybenzoic acid.
[0024] [ka]
[0025] Other specific examples of oxycarbonyl units that can be used include structural units derived from m-hydroxybenzoic acid, etc.
[0026] The liquid crystal polyester resin (A) of the present invention contains, as dicarbonyl units, 10 to 40 mol % of structural units derived from aromatic dicarboxylic acids relative to 100 mol % of all structural units of the liquid crystal polyester resin (A). If it is less than 10 mol %, liquid crystallinity is impaired, making melt molding difficult. It is preferably 15 mol % or more, more preferably 20 mol % or more. On the other hand, if it is more than 40 mol %, melt molding is difficult. Also, from the viewpoint of stringiness resistance, it is preferably 35 mol % or less, more preferably 30 mol % or less. Examples of structural units derived from aromatic dicarboxylic acids include structural units derived from terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 3,3'-diphenyldicarboxylic acid, 2,2'-diphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-4,4'-dicarboxylic acid, 1,2-bis(2-chlorophenoxy)ethane-4,4'-dicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and the like. From the viewpoints of easy availability and an excellent moldable temperature range, it is preferable to use structural units derived from terephthalic acid and isophthalic acid.
[0027] From the viewpoint of excellent stringiness resistance during high-temperature molding, the liquid crystal polyester resin (A) of the present invention preferably contains 0.01 mol% or more of the structural unit (II) as a structural unit derived from an aromatic dicarboxylic acid, preferably 0.05 mol% or more, more preferably 0.1 mol% or more, relative to 100 mol% of all structural units of the liquid crystal polyester resin (A). In addition, it is preferable to contain 5 mol% or less of the structural unit (II), more preferably 3 mol% or less, and even more preferably 1.5 mol% or less. The structural unit (II) is a structural unit derived from isophthalic acid. The structural unit (II) has a bent structure and disturbs the linearity of the molecular chain, so that during heating and retention, the entanglement of the molecular chains of the liquid crystal polyester resin (A) is promoted, and the stringiness resistance during high-temperature molding is improved. The above-mentioned preferable range can accentuate the effects of the present invention.
[0028] [ka]
[0029] From the viewpoint of excellent threading resistance during high-temperature molding, the liquid crystal polyester resin (A) of the present invention preferably contains 5 mol% or more of the structural unit (III) as a structural unit derived from an aromatic dicarboxylic acid, based on 100 mol% of all structural units of the liquid crystal polyester resin (A), preferably contains 10 mol% or more, and more preferably contains 15 mol% or more. Also, it is preferably 35 mol% or less, more preferably 30 mol% or less, and even more preferably 25 mol% or less. The structural unit (III) is a structural unit derived from terephthalic acid.
[0030] [ka]
[0031] As other dicarbonyl units, structural units derived from aliphatic dicarboxylic acids such as adipic acid, azelaic acid, sebacic acid, dodecanedioic acid, and hexahydroterephthalic acid; and structural units derived from alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid and 1,3-cyclohexanedicarboxylic acid can be used within the scope that does not impair the effects of the present invention.
[0032] In the liquid crystal polyester resin (A) of the present invention, from the viewpoint of excellent stringiness resistance during high-temperature molding, the ratio ([II] / [I]) of the content of the structural unit (I) and the structural unit (II) to 100 mol% of all structural units of the liquid crystal polyester resin (A) is preferably less than 1. By setting it in this range, the structural unit (II) is sufficiently incorporated into the polymer chain and disturbs the linearity of the molecular chain, so that the entanglement of the molecular chains of the liquid crystal polyester resin (A) is promoted during heating retention, and the stringiness resistance during high-temperature molding is improved. On the other hand, the lower limit of [II] / [I] is not particularly limited, and may be 0.005 or more. [II] / [I] is preferably 0.01 or more, more preferably 0.05 or more.
[0033] From the viewpoint of excellent stringiness resistance during high-temperature molding, the liquid crystal polyester resin (A) of the present invention preferably has a relationship in the content of structural units (II) and (III) relative to 100 mol% of all structural units of the liquid crystal polyester resin (A) that satisfies the following formula (d): By setting the content within this range, the structural unit (II) is sufficiently incorporated into the polymer chain and disrupts the linearity of the molecular chain, thereby promoting entanglement of the molecular chains of the liquid crystal polyester resin (A) during heating retention, and improving stringiness resistance during high-temperature molding. 0.92<[III] / ([II]+[III])<1 ···(d) ([II] and [III] indicate the contents (mol %) of the following structural units (II) and (III) relative to 100 mol % of all structural units in the liquid crystal polyester resin (A).) The liquid crystal polyester resin (A) of the present invention contains, as dioxy units, 10 to 40 mol % of structural units derived from aromatic diol, based on 100 mol % of all structural units of the liquid crystal polyester resin (A). If it is less than 10 mol %, melt moldability becomes difficult. It is preferably 15 mol % or more, and more preferably 20 mol % or more. On the other hand, if it is more than 40 mol %, the stringing resistance decreases. It is preferably 35 mol % or less, and more preferably 30 mol % or less. Examples of structural units derived from aromatic diols include structural units derived from 4,4'-dihydroxybiphenyl, hydroquinone, resorcinol, t-butylhydroquinone, phenylhydroquinone, chlorohydroquinone, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 3,4'-dihydroxybiphenyl, 2,2-bis(4-hydroxyphenyl)propane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfide, and 4,4'-dihydroxybenzophenone.
[0034] From the viewpoint of excellent threading resistance during high-temperature molding, the liquid crystal polyester resin of the present invention preferably contains 2 mol% or more of structural unit (V) as a structural unit derived from aromatic diol, preferably 5 mol% or more, more preferably 8 mol% or more, based on 100 mol% of all structural units of liquid crystal polyester resin (A). Also, it is preferably 20 mol% or less, more preferably 18 mol% or less, and even more preferably 16 mol% or less. The structural unit (V) is a structural unit derived from hydroquinone.
[0035] [ka]
[0036] From the viewpoint of excellent threading resistance during high-temperature molding, the liquid crystal polyester resin (A) of the present invention preferably contains 2 mol% or more of the structural unit (VI) as a structural unit derived from an aromatic diol, preferably 4 mol% or more, and more preferably 6 mol% or more, based on 100 mol% of all structural units of the liquid crystal polyester resin (A). Also, it is preferably 20 mol% or less, more preferably 17 mol% or less, and even more preferably 14 mol% or less. The structural unit (VI) is a structural unit derived from 4,4'-dihydroxybiphenyl.
[0037] [ka]
[0038] As other dioxy units, structural units derived from aliphatic diols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, and neopentyl glycol; and structural units derived from alicyclic diols such as 1,4-cyclohexanediol and 1,4-cyclohexanedimethanol can be used within the scope that does not impair the effects of the present invention.
[0039] The liquid crystal polyester resin (A) of the present invention preferably contains all of the structural units (I) to (VI) in the above ranges, because the resin has better stringiness resistance during high-temperature molding. In addition, from the viewpoint of not impairing the effects of the present invention, the total amount of the structural units (I) to (VI) is preferably 99 mol % or more, more preferably 99.5 mol % or more, and more preferably 100 mol %.
[0040] In addition to the above structural units (I) to (VI), the liquid crystal polyester resin (A) may contain structural units produced from p-aminobenzoic acid, p-aminophenol, etc., within the scope of the present invention.
[0041] The monomers serving as raw materials for forming each of the structural units described above are not particularly limited as long as they have a structure capable of forming each of the structural units. In addition, acylation products of the hydroxyl groups of such monomers, esterification products of the carboxyl groups, acid halides, acid anhydrides and other carboxylic acid derivatives may be used.
[0042] The method for calculating the content of each structural unit in the liquid crystal polyester resin (A) is as follows. First, the liquid crystal polyester resin is pulverized, and then tetramethylammonium hydroxide is added. The content can be determined by pyrolysis GC / MS measurement using a Shimadzu GCMS-QP5050A. The content of structural units that are not detected or are below the detection limit is calculated as 0 mol%.
[0043] From the viewpoint of heat resistance, the melting point (Tm) of the liquid crystal polyester resin (A) is preferably 280° C. or higher, more preferably 300° C. or higher, and even more preferably 320° C. or higher. On the other hand, from the viewpoint of processability, the melting point (Tm) of the liquid crystal polyester resin is preferably 370° C. or lower, more preferably 360° C. or lower, and even more preferably 350° C. or lower.
[0044] From the viewpoint of heat resistance, the melt viscosity of the liquid crystal polyester resin (A) is preferably 3 Pa·s or more, and more preferably 5 Pa·s or more, while from the viewpoint of fluidity, the melt viscosity of the liquid crystal polyester resin (A) is preferably 50 Pa·s or less, more preferably 30 Pa·s or less, and even more preferably 20 Pa·s or less.
[0045] The melt viscosity is a value measured by a Koka type flow tester at a temperature of the melting point (Tm) of the liquid crystal polyester resin (A) + 20° C. and under the condition of a shear rate of 1000 / sec.
[0046] <Method for producing liquid crystal polyester resin (A)> The liquid crystal polyester resin (A) of the present invention can be produced by copolymerizing monomers that provide the structural units (I) to (VI) in a content within the above-mentioned range, or by blending two or more liquid crystal polyester resins obtained by copolymerizing the structural units (I) to (VI) in a content outside the above-mentioned range, so that the structural units (I) to (VI) fall within the above-mentioned range. From the viewpoint of excellent stringiness resistance without inheriting the properties of the liquid crystal polyester resin before blending, the method of copolymerizing monomers that provide the structural units (I) to (VI) in a content within the above-mentioned range is preferred.
[0047] The method for producing the liquid crystal polyester resin (A) of the present invention is not particularly limited, and the resin can be produced in accordance with a known polyester polycondensation method. However, from the viewpoint of excellent thread-drawing resistance, for example, in the case of a liquid crystal polyester resin consisting of structural units derived from p-hydroxybenzoic acid, structural units derived from 6-hydroxy-2-naphthoic acid, structural units derived from 4,4'-dihydroxybiphenyl, structural units derived from hydroquinone, and structural units derived from terephthalic acid and isophthalic acid, a method of reacting p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 4,4'-dihydroxybiphenyl, hydroquinone, terephthalic acid and isophthalic acid with acetic anhydride to acetylate the phenolic hydroxyl groups, followed by deacetic acid polymerization to produce a liquid crystal polyester resin is preferred.
[0048] <Plate-shaped filler (B)> The liquid crystal polyester resin composition of the present invention contains 10 to 100 parts by weight of the plate-like filler (B) relative to 100 parts by weight of the liquid crystal polyester resin (A). If it is less than 10 parts by weight, the stringiness resistance decreases, and if it is more than 100 parts by weight, the molding processability decreases. From the viewpoint of excellent stringiness resistance during high-temperature molding, the plate-like filler (B) is preferably 15 parts by weight or more, more preferably 20 parts by weight or more, relative to 100 parts by weight of the liquid crystal polyester resin (A). Also, it is preferably 80 parts by weight or less, more preferably 60 parts by weight or less.
[0049] Examples of the plate-like filler (B) used in the present invention include mica, talc, kaolin, glass flakes, clay, molybdenum disulfide, and wollastonite, etc. Mica is particularly preferred from the viewpoint of excellent fluidity and resistance to stringiness during high-temperature molding.
[0050] The plate-like filler (B) in the liquid crystal polyester resin composition of the present invention is characterized in that the particle size at 70% cumulative frequency (hereinafter sometimes simply referred to as D70) obtained from a cumulative particle size distribution curve is 25 to 45 μm, and the particle size at 30% cumulative frequency (hereinafter sometimes simply referred to as D30) is 15 to 25 μm.
[0051] FIG. 1 shows a schematic diagram of the cumulative particle size distribution curve of the plate-like filler in the liquid crystal polyester resin composition. The cumulative particle size distribution curve shown by the solid line in FIG. 1 is the cumulative distribution curve of the plate-like filler in the liquid crystal polyester resin composition of the present invention, and it can be seen that by setting D70 and D30 within the above range, the particle size distribution becomes wider than that of the conventional composition shown by the dotted line. As in the present invention, by incorporating a plate-like filler with a wide particle size into the liquid crystal polyester composition, the orientation of the liquid crystal polyester resin in the molded product can be moderately disturbed, and especially the orientation of the resin present from the sprue apex of the molded product to the nozzle tip of the molding machine is disturbed, so that the relevant part is less likely to stretch into a thread when the mold is opened even under high temperature, high shear and high cycle conditions. In addition, if the particle size is within the above range, the orientation of the resin is not significantly disturbed during the flow of the molten resin, so the inherent fluidity of the liquid crystal polyester resin is also guaranteed. Therefore, it is possible to achieve both stringing resistance and fluidity at a high level. If D70 or D30 is outside the above range, the stringing resistance decreases. From the viewpoint of excellent stringiness resistance during high-temperature molding, the D70 range is preferably from 28 to 42 μm, more preferably from 30 to 40 μm, and the D30 range is preferably from 16 to 24 μm, more preferably from 17 to 22 μm.
[0052] From the viewpoint of excellent stringiness resistance during high-temperature molding, the particle size at 90% cumulative frequency (hereinafter, sometimes simply referred to as D90) obtained from the cumulative particle size distribution curve of the plate-like filler (B) in the liquid crystal polyester resin composition of the present invention is preferably 40 to 60 μm. More preferably, it is 43 to 53 μm, and even more preferably, it is 45 to 51 μm. Furthermore, by setting D90 within the above range, gate clogging due to a large particle size plate-like filler is unlikely to occur, and molding stability is improved.
[0053] Specifically, when injection molding a molded product having an extremely small gate portion, such as a pinpoint gate, by setting D90 within the above range, clogging of the gate due to large particle size plate-like filler is unlikely to occur, the entire cavity is filled with resin, so that so-called short shots are unlikely to occur, and molding stability is improved.
[0054] The values of D90, D70 and D30 of the plate-like filler (B) in the liquid crystal polyester resin composition of the present invention are obtained by the following method. 3 g of the liquid crystal polyester resin composition is heated in air at 550 ° C for 3 hours to remove the liquid crystal polyester resin (A) component, and the residue remaining as a non-combustible material is obtained as the plate-like filler (B). 100 mg of the obtained plate-like filler (B) is weighed and thoroughly dispersed in 6 g of deionized water together with 10 mg of a surfactant to obtain a measurement dispersion. The measurement dispersion is added to a laser diffraction type particle size distribution measuring device (Microtrac MT3300EXII) manufactured by Nikkiso Co., Ltd. until it reaches a measurable concentration, and ultrasonic dispersion is performed in the measuring device at 30 W for 60 seconds, and then the particle size at which the cumulative frequency from the small particle size side of the particle size distribution measured in a measurement time of 10 seconds is 30% is defined as D30, the particle size at which it is 70% is defined as D70, and the particle size at which it is 90% is defined as D90. The refractive index during measurement is 1.52, and the refractive index of the medium (deionized water) is 1.33.
[0055] From the viewpoint of facilitating the setting of the above-mentioned D70 and D30 in the appropriate range, it is preferable to blend 10 to 100 parts by weight of a plate-like filler (B) having a particle size (D70) of 30 to 55 μm at cumulative frequency 70% and a particle size (D30) of 20 to 30 μm at cumulative frequency 30% with respect to 100 parts by weight of a liquid crystal polyester resin (A), and to produce a liquid crystal polyester resin composition by the method described later in <Method of producing liquid crystal polyester resin composition>. Note that the D70 and D30 described in this paragraph indicate the D70 and D30 of the plate-like filler (B) before blending. From the viewpoint of facilitating the setting of the above-mentioned D70 and D30 in the appropriate range, the range of D70 is more preferably 35 to 50 μm, and more preferably 37 to 46 μm. The range of D30 is more preferably 22 to 30 μm, and more preferably 22 to 27 μm. By including the plate-like filler (B) having the above particle size and by using the preferred production method described below in the <Production method of liquid crystal polyester resin composition>, it becomes easy to control the particle size of the plate-like filler (B) in the liquid crystal polyester resin composition.
[0056] <Fillers other than plate-shaped filler (B)> The liquid crystal polyester resin composition of the present invention contains the liquid crystal polyester resin (A) and the plate-like filler (B), but may contain fillers other than the plate-like filler (B) to impart other properties. The filler used in the present invention is not particularly limited, and examples thereof include fibrous, whisker-like, plate-like, powdery, and granular fillers. Specifically, examples of fibrous and whisker-like fillers include glass fibers, PAN-based and pitch-based carbon fibers, stainless steel fibers, metal fibers such as aluminum fibers and brass fibers, organic fibers such as aromatic polyamide fibers and liquid crystal polyester fibers, gypsum fibers, ceramic fibers, asbestos fibers, zirconia fibers, alumina fibers, silica fibers, titanium oxide fibers, silicon carbide fibers, rock wool, potassium titanate whiskers, barium titanate whiskers, aluminum borate whiskers, silicon nitride whiskers, and needle-shaped titanium oxide. Examples of powdery and granular fillers include silica, glass beads, titanium oxide, zinc oxide, calcium polyphosphate, and graphite.
[0057] The type of glass fiber in the filler is not particularly limited so long as it is one generally used for reinforcing resins, and examples thereof include chopped strands of long fiber type or short fiber type, milled fiber, and the like.
[0058] The surface of the filler may be treated with a known coupling agent (e.g., a silane coupling agent, a titanate coupling agent, etc.) or other surface treatment agent. The glass fiber may be coated or bundled with a thermoplastic resin such as an ethylene / vinyl acetate copolymer or a thermosetting resin such as an epoxy resin. The fillers used in the present invention may be used in combination of two or more kinds.
[0059] The liquid crystal polyester resin composition of the present invention may further contain conventional additives selected from antioxidants, heat stabilizers (e.g., hindered phenols, hydroquinone, phosphites, thioethers, and their substitutes), ultraviolet absorbers (e.g., resorcinol, salicylate), color inhibitors such as phosphites and hypophosphites, lubricants and mold release agents (montanic acid and its metal salts, its esters, its half esters, stearyl alcohol, stearamide, and polyethylene wax), colorants containing dyes or pigments, conductive agents or colorants such as carbon black, crystal nucleating agents, plasticizers, flame retardants (bromine-based flame retardants, phosphorus-based flame retardants, red phosphorus, silicone-based flame retardants, etc.), flame retardant assistants, and antistatic agents, within the scope of the present invention.
[0060] <Method of producing liquid crystal polyester resin composition> The method of blending the plate-like filler (B) and other additives into the liquid crystal polyester resin (A) can be, for example, a dry blending method of blending the plate-like filler (B) and other solid additives into the liquid crystal polyester resin (A), a solution blending method of blending the plate-like filler (B) and other liquid additives into the liquid crystal polyester resin (A), a method of adding the plate-like filler (B) and other additives during polymerization of the liquid crystal polyester resin (A), or a method of melt-kneading the plate-like filler (B) and other additives into the liquid crystal polyester resin (A). From the viewpoint of making it easier to set D70 and D30 in the appropriate range, the melt-kneading method is preferred.
[0061] A known method can be used for melt kneading. For example, a Banbury mixer, a rubber roll machine, a kneader, a single-screw or twin-screw extruder, etc. can be mentioned. From the viewpoint of easily setting D70 and D30 in the appropriate range, a method of melt kneading using a twin-screw extruder is preferred. In particular, a method of melt kneading using a twin-screw extruder with L / D>30, where L is the screw length and D is the screw diameter, is particularly preferred. The screw length here refers to the length from the position where the raw material is supplied at the base of the screw to the tip of the screw. The upper limit of L / D of the twin-screw extruder is 150, and preferably, one with L / D exceeding 30 and not exceeding 100 can be used.
[0062] From the viewpoint of easily setting D70 and D30 in appropriate ranges, the set temperature of the cylinder of the extruder during melt kneading is preferably set in the range of −10° C. to +30° C., more preferably −10° C. to +20° C., and even more preferably −5° C. to +5° C., of the melting point of the liquid crystal polyester resin (A).
[0063] From the viewpoint of easily setting D90 in an appropriate range, the cylinder temperature of the extruder during melt kneading is preferably set in the range of -20°C to +15°C (the melting point of the liquid crystal polyester resin (A)) at 24% to 62% of the total screw length, more preferably -15°C to +10°C (the melting point of the liquid crystal polyester resin (A)), and even more preferably -10°C to +5°C (the melting point of the liquid crystal polyester resin (A)).
[0064] From the viewpoint of easily setting D70 and D30 in the appropriate ranges, the rotational peripheral speed (m / min) of the screw during melt kneading is preferably 10 to 30 m / min, more preferably 13 to 23 m / min, and even more preferably 15 to 22 m / min.
[0065] From the viewpoint of easily setting D90 in an appropriate range, the rotational peripheral speed (m / min) of the screw during melt kneading is preferably 10 to 50 m / min, more preferably 13 to 45 m / min, and even more preferably 15 to 40 m / min. The rotational peripheral speed of the screw (m / min) can be calculated by multiplying the screw diameter (m) by the circular constant (pi) by the rotation speed (rpm).
[0066] In the present invention, the screw configuration used in the twin-screw extruder is a combination of full flight and kneading discs. From the viewpoint of easily setting D90, D70, and D30 in appropriate ranges, the ratio of the total length of the kneading discs (hereinafter sometimes referred to as "kneading zone") to the total length of the screws is preferably in the range of 5 to 50%, more preferably in the range of 10 to 40%, and most preferably in the range of 20 to 30%.
[0067] The kneading method includes 1) a method of kneading the liquid crystal polyester resin (A), the plate-like filler (B) and other additives all at once from the feeder (lump-kneading method), 2) a method of kneading the liquid crystal polyester resin (A) and other additives from the feeder, and then adding the plate-like filler (B) from the side feeder (side feed method), and 3) a liquid crystal polyester composition (master pellet) containing a high concentration of the liquid crystal polyester resin (A), the plate-like filler (B) and other additives is prepared, and then the master pellet is kneaded with the liquid crystal polyester resin (A), the plate-like filler (B) and other additives to a specified concentration (master pellet method). From the viewpoint of making it easier to set D90, D70, and D30 in the appropriate range, the lump-kneading method described in 1) above is preferred.
[0068] The liquid crystal polyester resin composition of the present invention satisfies two or more of the following items (V), (W), (X), (Y), and (Z), which makes it easy to set D90, D70, and D30 within appropriate ranges. It is preferable to satisfy three or more of the items (V), (W), (X), (Y), and (Z). It is more preferable to satisfy two or three items including at least (Z). (V): Regarding the cylinder temperature of the extruder during melt kneading, as described above, the screw length is set to 24% to 62% of the total screw length within the range of -20°C to +15°C of the melting point of the liquid crystal polyester resin (A). (W): The rotational peripheral speed (m / min) of the screw during melt kneading is set to 10 to 50 m / min as described above. (X): Two or more types of plate-like filler (B) are mixed with the liquid crystal polyester resin (A) so that D90, D70, and D30 are within appropriate ranges. (Y): The plate-like filler (B) is classified using a sieve or the like so that D90, D70, and D30 fall within appropriate ranges, and is then mixed with the liquid crystal polyester resin (A). (Z): When used in a twin-screw extruder, the screw configuration is a combination of full flight and kneading discs, and the ratio of the total length of the kneading discs (hereinafter sometimes referred to as "kneading zone") to the total length of the screw is in the range of 5 to 50%, preferably in the range of 10 to 40%, and more preferably in the range of 20 to 30%. Here, in item (V), it is more preferable that the cylinder temperature of the extruder during melt kneading is in the range of −15°C to +10°C of the melting point of the liquid crystal polyester resin (A) for a screw length that is 24% to 62% of the total screw length, and even more preferably in the range of −10 to +5°C of the melting point. In item (W), the rotational peripheral speed (m / min) of the screw during melt-kneading is more preferably in the range of 13 to 45 m / min, and even more preferably in the range of 15 to 40 m / min.
[0069] <Molded products> The liquid crystal polyester resin composition of the present invention can be processed into a molded product having excellent surface appearance (color tone), mechanical properties, and heat resistance by a molding method such as ordinary injection molding, extrusion molding, press molding, solution cast film formation, spinning, etc. The molded product here includes injection molded products, extrusion molded products, press molded products, sheets, pipes, various films such as unstretched films, uniaxially stretched films, and biaxially stretched films, and various fibers such as unstretched yarns and ultrastretched yarns. In particular, injection molding is preferable from the viewpoint of processability.
[0070] The molded product obtained by molding the liquid crystal polyester resin composition of the present invention can be preferably used as an electric / electronic part. Examples of electric / electronic parts include flexible printed circuit boards, laminated circuit boards, printed wiring boards and three-dimensional circuit boards used in antennas of mobile communication / electronic devices such as personal computers, GPS-equipped devices, mobile phones, millimeter wave and quasi-millimeter wave radars such as collision prevention radars, tablets and smartphones; lamp reflectors and lamp sockets such as LEDs, communication base station small cells and microcell members of mobile communication terminals, antenna covers, housings, sensors, actuator parts of camera modules, connectors, relay cases and bases, switches, coil bobbins, capacitors, etc. Among them, connectors, relays, switches, coil bobbins, actuator parts of camera modules, etc. are useful. EXAMPLES
[0071] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The liquid crystal polyester resin (A) described in the production examples was evaluated in the following items (1) to (3), and the results are shown in Table 1.
[0072] (1) Composition analysis of liquid crystal polyester resin (A) To 0.1 mg of the ground liquid crystal polyester resin, 2 μL of a 25% methanol solution of tetramethylammonium hydroxide was added, and pyrolysis GC / MS measurement was performed using a Shimadzu GCMS-QP5050A to determine the composition ratio of each component in the liquid crystal polyester resin.
[0073] (2) Melting point (Tm) measurement of liquid crystal polyester resin (A) Using a differential scanning calorimeter DSC-7 (PerkinElmer), the liquid crystal polyester resin was heated from room temperature at a temperature increase rate of 20°C / min to observe the endothermic peak temperature (Tm1), and then held at a temperature of Tm1+20°C for 5 minutes. The resin was then cooled to room temperature at a temperature decrease rate of 20°C / min, and the endothermic peak temperature observed when the resin was heated again at a temperature increase rate of 20°C / min was determined as the melting point (Tm).
[0074] (3) Melt Viscosity of Liquid Crystal Polyester Resin (A) The melt viscosity of the liquid crystal polyester resin was measured at Tm+20° C. and a shear rate of 1000 / s using a high-performance flow tester CFT-500D (orifice 0.5φ×10 mm) (manufactured by Shimadzu Corporation).
[0075] [Production Example 1] In a 5L reaction vessel equipped with an agitator and a distillation tube, 808 parts by weight of p-hydroxybenzoic acid (HBA), 88 parts by weight of 6-hydroxy-2-naphthoic acid (HNA), 229 parts by weight of 4,4'-dihydroxybiphenyl (DHB), 161 parts by weight of hydroquinone (HQ), 428 parts by weight of terephthalic acid (TPA), 19 parts by weight of isophthalic acid (IPA) and 1278 parts by weight of acetic anhydride (1.07 equivalents of phenolic hydroxyl groups in total) were charged, and the mixture was reacted at 145°C for 120 minutes while stirring under a nitrogen gas atmosphere, and then the temperature was raised from 145°C to 360°C over 4 hours. Thereafter, the polymerization temperature was maintained at 360°C, the pressure was reduced to 1.0 torr (133 Pa) over 1.0 hour, and the reaction was continued until the polymerization was completed when a predetermined stirring torque was reached. Next, the polymer was discharged in the form of strands through a die having one circular discharge port with a diameter of 6 mm, and pelletized with a cutter to obtain a liquid crystal polyester resin (A-1).
[0076] [Production Example 2] Liquid crystal polyester resin (A-2) was obtained in the same manner as in Example 1, except that the monomer charge was changed to 931 parts by weight of p-hydroxybenzoic acid (HBA), 251 parts by weight of 4,4'-dihydroxybiphenyl (DHB), 99 parts by weight of hydroquinone (HQ), 284 parts by weight of terephthalic acid (TPA), 90 parts by weight of isophthalic acid (IPA) and 1227 parts by weight of acetic anhydride (1.07 equivalents of the total of phenolic hydroxyl groups).
[0077] [Table 1]
[0078] A plate-like filler (B) was further blended with the liquid crystal polyester resin (A) obtained in Production Examples 1 and 2 to prepare a liquid crystal polyester resin composition. The plate-like filler (B) used in each Example and Comparative Example is shown below. The particle size (D70 and D30) of the plate-like filler (B) before blending was measured by the same method as described in (4) below.
[0079] Filler (B) (B-1) Mica "AB-25S" manufactured by Yamaguchi Mica Co., Ltd. (Particle size before blending: D70 = 30 μm, D30 = 17 μm) (B-2) Mica "A-41S" manufactured by Yamaguchi Mica Co., Ltd. (Particle size before blending: D70 = 55 μm, D30 = 33 μm) (B-3) Mica "J-31M" manufactured by Yamaguchi Mica Co., Ltd. was sieved using a 400 mesh sieve to obtain the particle size described below, and the mica powder remaining on the sieve was used. (Particle size before blending: D70 = 40 μm, D30 = 24 μm) (B-4) Mica "J-31M" manufactured by Yamaguchi Mica Co., Ltd. (Particle size before blending: D70 = 41 μm, D30 = 19 μm)
[0080] [Examples 1, 2, and 6, and Comparative Examples 1 and 2] The liquid crystal polyester resin (A) and the plate-shaped filler (B) obtained in each manufacturing example were introduced into a twin-screw extruder (TEX-30α, manufactured by Japan Steel Works) with a screw diameter of 30 mm and L / D 35 and equipped with a co-rotating vent, in the amounts shown in Table 2. The cylinder temperature was set to the melting point of the liquid crystal polyester resin (A), and the liquid crystal polyester resin (A) and the plate-shaped filler (B) were added all at once from the bottom feeder (lump-mixing method), and the screw configuration was made to incorporate a kneading zone, with the ratio being 25% of the total screw length. The melt mixing was performed under the extrusion conditions of a screw rotational peripheral speed of 19 m / min, and the mixture was discharged in the form of a strand, solidified through a cooling bath, and then pelletized by a strand cutter.
[0081] [Example 3] The liquid crystal polyester resin (A) and the plate-like filler (B) obtained in each production example were introduced into a twin-screw extruder in the amounts shown in Table 2, and pellets were obtained in the same manner as in Example 1, except that the screw rotation peripheral speed was set to 38 m / min.
[0082] [Example 4] The liquid crystal polyester resin (A) and plate-shaped filler (B) obtained in each manufacturing example were introduced into a twin-screw extruder in the amounts shown in Table 2, and pellets were obtained in the same manner as in Example 1, except that the resin temperature from 24% to 62% of the total length of the screw was set to the melting point of the liquid crystal polyester resin (A) -10°C, and the parts less than 24% and more than 62% of the total length of the screw were set to the melting point of the liquid crystal polyester resin (A).
[0083] [Example 5] The liquid crystal polyester resin (A) and plate-like filler (B) obtained in each manufacturing example were introduced into a twin-screw extruder in the amounts shown in Table 2, and pellets were obtained in the same manner as in Example 1, except that the cylinder temperature was set to the melting point of the liquid crystal polyester resin (A) -10°C from 24% to 62% of the total screw length, the melting point of the liquid crystal polyester resin (A) was set to the portion less than 24% and more than 62% of the total screw length, and the screw rotation peripheral speed was set to 38 m / min.
[0084] [Comparative Example 3] The liquid crystal polyester resin (A) and the plate-shaped filler (B) obtained in the manufacturing example were introduced into a twin-screw extruder (TEX-30α, manufactured by Japan Steel Works) with a screw diameter of 30 mm and L / D 35 and equipped with a co-rotating vent, in the amounts shown in Table 2. The cylinder temperature was set to the melting point of the liquid crystal polyester resin (A) + 10°C, the liquid crystal polyester resin (A) was fed from the bottom feeder, and the plate-shaped filler (B) was fed from the intermediate feeder (side feeder) built into the center of the extruder (side feed method), and the kneading zone was built in the middle of the side feeder to the discharge port, with the ratio being 15% of the total screw length. Melt mixing was performed under extrusion conditions of a screw rotational peripheral speed of 14 m / min, and the mixture was discharged in the form of a strand, solidified through a cooling bath, and then pelletized by a strand cutter.
[0085] The pellets obtained by the above method were used to carry out the following evaluations (4) to (6), and the results are shown in Table 2.
[0086] (4) D90, D70 and D30 of the plate-like filler (B) in the liquid crystal polyester resin composition 3 g of the liquid crystal polyester resin composition was heated in air at 550°C for 3 hours to remove the liquid crystal polyester resin (A) component, and the residue remaining as a non-combustible material was obtained as a plate-like filler (B). 100 mg of the obtained plate-like filler (B) was weighed out and thoroughly dispersed in 6 g of deionized water together with 10 mg of a surfactant to obtain a dispersion liquid for measurement. The dispersion liquid for measurement was added to a laser diffraction type particle size distribution meter (Microtrac MT3300EXII) manufactured by Nikkiso Co., Ltd. until it reached a measurable concentration, and after ultrasonic dispersion for 60 seconds at 30 W in the measuring device, the particle size at which the cumulative frequency from the small particle size side of the particle size distribution measured in a measurement time of 10 seconds was calculated as D30, the particle size at which the cumulative frequency was 30% from the small particle size side was calculated as D70, and the particle size at which the cumulative frequency was 90% was calculated as D90. The refractive index during measurement was 1.52, and the refractive index of the medium (deionized water) was 1.33. The obtained D30, D70 and D90 are shown in Table 2 as "particle size of each cumulative frequency in the composition (B)."
[0087] (5) Evaluation of stringiness during high-temperature molding The liquid crystal polyester resin was dried at 150°C for 3 hours using a hot air dryer, and then fed into a TR30EHA injection molding machine (manufactured by Sodick) and subjected to high temperature and high speed injection conditions, i.e., cylinder temperature was set to the melting point of the liquid crystal polyester resin + 30°C, mold temperature was set to 110°C, and a mold capable of molding a molded product of 30 mm wide x 30 mm long x 0.5 mm thick was used. The molding pressure was adjusted so that the resin hit the end of the mold, and a dwell pressure of 45 MPa was applied for 0.5 seconds, the injection speed was set to 200 mm / s, and the molding cycle was set to 6 seconds. Continuous molding under high temperature and high injection conditions such as these conditions resulted in significant effects of the orientation of the liquid crystal polyester resin, the generated gas, and the entrapment of air during molding, making stringing more likely to occur. During 100 continuous molding shots, the number of pieces that had stringing from the tip of the spool was counted, and the "occurrence rate (%)" of stringing was calculated. In addition, when stringing occurred, the length of the stringing portion generated from the tip of the spool was measured, and the average value was calculated as the "length (mm)" of stringing. The obtained values are shown in "stringing resistance" in Table 2 as "occurrence rate (%)" and "length (mm)". The smaller the occurrence rate and length, the better the stringing resistance.
[0088] (6) Gate clogging evaluation The liquid crystal polyester resin composition was dried at 150°C for 3 hours using a hot air dryer, and then subjected to a TR30EHA injection molding machine (manufactured by Sodick). The cylinder temperature was set to the melting point of the liquid crystal polyester resin + 10°C, the nozzle temperature was set to the melting point of the liquid crystal polyester resin only, and the mold temperature was set to 110°C. The injection pressure was set to 100MPa, the speed to 150mm / sec, and the molded product had a box-shaped part with an outer dimension of 5.0mm x 5.0mm and a thickness of 0.5mm, and a strip part with a width of 5.0mm and a thickness of 0.2mm, as shown in Figure 2, and a gate hole of φ0.2mm. After adjusting the conditions so that the length of the strip part was 20mm, 50 shots were continuously molded, and the number of short shots in which the length of the strip part was less than 20mm and could not be molded was evaluated. In this measurement, if the gate is clogged due to the aggregation of the plate-like filler, the molded product will not be filled and short shots will occur. The number of short shots was evaluated as gate clogging, and the fewer the short shots, the less likely gate clogging occurred, which was considered to be excellent.
[0089] [Table 2]
[0090] From the results in Tables 1 and 2, it is understood that by controlling the D70 and D30 of the flake-like filler (B) in the liquid crystal polyester resin composition to fall within a specific range, a liquid crystal polyester resin composition having excellent stringiness resistance can be obtained. [Industrial Applicability]
[0091] The liquid crystal polyester resin composition of the present invention has excellent resistance to stringiness during high-temperature molding, and therefore can be suitably used for connectors, relays, switches, coil bobbins, and actuator parts for camera modules, and is particularly suitable for connectors, which have become thinner and finer pitch in recent years. [Explanation of symbols]
[0092] 1. Particle size (μm) axis of plate-shaped filler: The arrow indicates the larger particle size side 2. Cumulative frequency (%) axis of plate-shaped filler 3. Example of particle size distribution curve where D70 is less than 25 μm and D30 is less than 15 μm 4. Example of particle size distribution curve where D70 is greater than 45 μm and D30 is greater than 25 μm 5. Example of particle size distribution curve with D70 of 25-45 μm and D30 of 15-25 μm 6. Box tubular part 7. Tanzaku section 8. Gate hole P. Perspective view of molded product Q. Side view of molded product R. Top view of molded product
Claims
1. The liquid crystal polyester resin composition contains 10 to 100 parts by weight of a plate-like filler (B) as an inorganic filler, based on 100 parts by weight of a liquid crystal polyester resin (A) which contains 20 to 80 mol % of structural units derived from an aromatic hydroxycarboxylic acid, 10 to 40 mol % of structural units derived from an aromatic diol, and 10 to 40 mol % of structural units derived from an aromatic dicarboxylic acid, based on 100 mol % of all structural units of the liquid crystal polyester resin (A), and the particle size of the plate-like filler (B) in the liquid crystal polyester resin composition satisfies the following requirement (α): Requirement (α): The particle size (D70) at 70% cumulative frequency, obtained from the cumulative particle size distribution curve of the plate-like filler (B) in the liquid crystal polyester resin composition, is 25 to 45 μm, and the particle size (D30) at 30% cumulative frequency is 15 to 25 μm.
2. The liquid crystal polyester resin composition according to claim 1, wherein the liquid crystal polyester resin (A) is a liquid crystal polyester resin containing the following structural unit (I) and satisfies the following formula (a). 1≦[I]≦20...(a) ([I] indicates the content (mol %) of each structural unit (I) described below relative to 100 mol % of all structural units in the liquid crystal polyester resin (A).) 【Chemistry 1】
3. The liquid crystal polyester resin composition according to claim 1, wherein the liquid crystal polyester resin (A) is a liquid crystal polyester resin containing the following structural units (I) and (II) and satisfies the following formulae (b) and (c). 0.01≦[II]≦5...(b) [II] / [I]<1...(c) ([I] and [II] indicate the contents (mol %) of the following structural units (I) and (II) relative to 100 mol % of all structural units in the liquid crystal polyester resin (A).) 【Chemistry 2】
4. The liquid crystal polyester resin composition according to claim 1, wherein the liquid crystal polyester resin (A) is a liquid crystal polyester containing the following structural units (II) and (III) and satisfies the following formula (d). 0.92<[III] / ([II]+[III])<1...(d) ([II] and [III] indicate the contents (mol %) of the following structural units (II) and (III) relative to 100 mol % of all structural units in the liquid crystal polyester resin (A).) 【Chemistry 3】
5. A molded article comprising the liquid crystal polyester resin composition according to any one of claims 1 to 4.
6. 6. The molded article according to claim 5, which is any one selected from the group consisting of a connector, a relay, a switch, a coil bobbin, and an actuator part of a camera module.
Citation Information
Patent Citations
Liquid crystal polyester resin composition
WO2013128887A1
Liquid crystal polyester composition, molded body, and connector
WO2017051883A1
Wholly aromatic liquid-crystal polyester resin
WO2018101214A1